Fabrication of Nanoporous Membrane-like Thin Layers via Block Copolymer Lithography of P2VP-b-PS Inverse Systems and their Potential Applications - Esmeraldo Paiva, Aislan (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2024)
The large-scale fabrication of nanoporous materials and substrates has generated significant research interest on account of the wide range of possible applications, including nanophotonics, optoelectronics, biomedical systems, and environmental sciences. Block copolymer (BCP) self-assembly is one such potential fabrication strategy, owing to its low cost and large-area production of periodically ordered domains. In this work, an alternative method to produce these porous materials is developed and studied. A cylinder-forming P2VP-b-PS BCP was chosen as a model system to generate highly ordered, vertically aligned PS cylinders in a P2VP matrix using a static solvent vapour annealing (SVA) process. The choice of solvent was carefully tailored by considering the balance in surface energetics of the substrate and the free surface. Moreover, the SVA process was optimized based on the different BCP molecular weights (MW) by fine-tuning the annealing time, temperature, and film thickness. The organized BCP films were obtained with cylinder diameters varying from ~ 35 to 400 nm, for the lowest and highest MW, respectively. The BCP films were subsequently infiltrated with metal ions and exposed to UV/ozone treatment, hence removing the polymeric material, and leaving a thin, patterned metal oxide layer. The influence of the metal cations on the infiltration process was analysed. It was observed that by increasing the oxidation state of the cation, better infiltration occurred. Moreover, X-ray photoelectron and Raman spectroscopies elucidated differences in the binding between the pyridinic nitrogen and the metal cations. As potential applications, the metal oxide structures were then utilised as hard masks on silicon for dry etching via (deep) reactive ion etching/inductively couple plasma (RIE-ICP), which produced silicon nanoporous membranes showing interesting properties for light absorption and thermal management. Finally, iron oxide structures also obtained through liquid-phase infiltration were applied to wastewater treatment via a Photo-Fenton reaction, leading to the degradation of a commonly used antibiotic, levofloxacin.
APPROVED
Keywords: Materials Engineering; Chemistry; Nanomaterials; Materials Science